The validity and reliability of teacher efficacy revisited in Malaysia secondary schools - Teh, Pei Ling; Lope Pihie, Zaidatol Akmaliah; Asimiran, Soaib; Foo, Say Fooi (Macrothink Institute, 2015)
In the education arena, teachers are the front line education workforce who educate the young people and bring positive impact to the new generation in a country. The roles of the teacher are pertinent in ensuring the success of students in pursuing their tertiary level from their common primary and secondary school education. With a high teacher efficacy level, a teacher is committed to teach more effectively and efficiently (Coladarci, 2010). Teacher’s efficacy research has been widely conducted in various international education settings but it is still important to revisit the validity and reliability of teacher efficacy in Malaysia context. Confirmatory factor analysis (CFA) was used to assess the uni-dimensionality, validity, reliability and fitness of teacher efficacy model. The teacher efficacy items have Cronbach’s alpha value greater than 0.70 for the reliability of three sub-constructs. The convergent and discriminant validity were also established as they fulfilled the criteria. Lastly, the teacher efficacy measurement model fulfilled the criteria for the goodness-of-fit in SEM and it is fit to embark to the structural modelling in SEM.